Investigating the relationship between integrated reporting and firm performance in a voluntary disclosure regime: insights from Bangladesh - Md. Shafiqul Islam (Emerald Publishing Limited, 2020)
The purpose of this study is observing the disclosure pattern of integrated reporting (IR) and investigating its relationship with a firm's operational, financial and market growth performance measured in the form of return on assets (ROA), return on equity (ROE) and market-to-book value ratio respectively in the voluntary disclosure regime of Bangladesh.This research is quantitative, based on a pooled-OLS regression analysis of 20 firms listed under ten different nonfinancial industries of the Dhaka Stock Exchange (DSE) for three financial years from 2015–2016 to 2017–2018, with 60 firm-year observations. A manual content analysis based on a structured integrated reporting disclosure index (IRDIN) measures the extent of disclosure in the corporate annual reports. The practical model consists of the dependent variable IRDIN and the independent variables ROA, ROE and market-to-book value ratio. The natural logarithm of total assets and financial leverage are the two controlling variables used in the model.The findings deduced from the empirical results indicate that the IRDIN is positively and significantly related to all three performance variables. Content analysis shows an increasing pattern of disclosure of the constructed index elements by the sample firms.A Small sample size may deter the generalization of the research findings in other voluntary disclosure regimes. Self-constructed IRDIN index scores may be affected by subjective judgment while assessing the annual reports.Capital market regulators can gain valuable insights regarding the suitability of implementing IR in Bangladesh as the results show a positive relationship of firm performance with the adoption of this revolutionary paradigm in corporate reporting.This study adds value to the existing limited literature of IR disclosure and firm performance in Bangladesh by incorporating content analysis and regression analysis to understand how firms respond to the demand of value creation by the stakeholders in a voluntary disclosure regime. This study captures sample firms from all the nonfinancial industries of Bangladesh with a unique IR index, which is the first of its kind.